Pelatihan Penggunaan ChatGPT dan Gemini Untuk Guru TK Dalam Membuat Media Pembelajaran Interaktif - Putri, Lia Umbari; Gultom, Karyawaty; Yesputra, Rolly (Smart Education, 2025)
Abstract: Kindergarten teachers play a crucial role in shaping the educational foundation of children, especially early childhood. Children's ability to adapt to technological innovation will greatly influence the quality of learning provided. Interactive learning media has proven effective in attracting children's attention, increasing their engagement, and providing a better understanding of learning concepts. However, all these processes require significant time, creativity, and resources. ChatGPT and Gemini are not just tools; they are partners in the educational world that can help teachers be more creative and innovative in developing learning methods. The benefits of using ChatGPT include its custom features that simplify the creation of teaching materials, while Gemini's unique